[PP.36.05]: INFLUENCE OF EXERCISE TRAINING ON TISSUE OXYGENATION IN PATIENTS WITH CHRONIC HEART FAILURE. (June 2015) - Dadashova>, G.>; Abdullayev, N.; Shirinova, E.
Abstract : Objective: Decrease of the tissue oxygenation has been noted in patients with heart failure (HF), developed after postinfarction aneurysm of the heart. It is connected both decrease of contractility of the heart and worsened function of vascular component of oxygen transport. The aim of the work was to study the influence of physical trainings on the possibility of improvement of tissue oxygenation. Design and method: 35 male patients with stable HF were prospectively randomized to a training group (T) (n = 21) or an inactive control group C(n = 14). At baseline (B) and after 4 weeks (wks) the data of tissue oxygenation [tension of skin oxygen (PO2) and time from oxygen inhalation to its increase in skin (L) was measured using transcutaneous oxygen monitor TCM2. Training were performed at 50% level from threshold loading. Results: During observation the indices of systolic and diastolic function of the heart were determined. These two groups of patients didn't differ with respect to age, heart rate, blood pressure and LV systolic and diastolic function at baseline. After 4 weeks of regular bicycle trainings in group T an increase of PO2 (45, 2 ± 2 mm Hg at B vs 51, 7 ± 2 after 2 weeks) and improvement of the time of tissue oxygenation (48, 9 ± 2, 9 sec at B vs 41, 0 ± 2, 04 after 4 weeks) have been noted. In group C these parameters did not change. Indices of systolic and diastolic functions in both groups did not change. Conclusions: Regular cycle ergometer training improves tissue oxygenation. Because of short-term program of physical rehabilitation central mechanisms of oxygen supply did not significantly change. Only vascular component of oxygen transport had a reaction. For real improvement of contractility function long-term training programs are necessary.